THE EFFECT OF COMBINED PROPOLIS EXTRACT AND VITAMIN E SUPPLEMENTATION ON IL-10 AND CRP - Fauziah Rezkiyati Sufath; Joko Wahyu Wibowo; Hadi Sarosa (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2026)
A high-fat diet induces oxidative stress and systemic inflammation, characterized by decreased the effects of propolis extract and vitamin E on IL-10 and CRP levels in male Wistar rats induced by a high-fat Interleukin-10 (IL-10) and increased C-Reactive Protein (CRP). This study aimed to evaluate diet. An experimental post-test only control group design was used, involving 30 rats divided into five groups: healthy control, high-fat diet control, vitamin E, propolis extract, and combination treatment. Interventions were administered for 14 days. Serum IL-10 and CRP levels were measured using ELISA and analysed using one-way ANOVA. The results showed that propolis extract and vitamin E significantly increased IL-10 levels (p < 0.05), indicating an improved anti-inflammatory response. However, CRP levels did not show significant differences among groups (p > 0.05). In conclusion, both treatments enhanced anti-inflammatory activity through IL-10 modulation but did not significantly affect CRP levels.